(k, m)-TYPE SLANT HELICES FOR THE NULL CARTAN CURVE WITH THE BISHOP FRAME IN E41 - Mazlum, Sumeyye Gur; Bektas, Mehmet (Honam Mathematical Soc, 2023)
In this paper, we obtain (k, m)-type slant helices for a null Cartan curve with the Bishop frame in Minkowski space E41 .
Keywords: Minkowski space-time; null Cartan curve; Bishop frame